Consumer Behavior Towards Technological Innovations: A Systematic Review - Vieira, Kelly Carvalho; Pinto, Guilherme Alcântara; Sugano, Joel Yutaka (Journal of Information Systems and Technology Management, 2022)
One of the biggest challenges facing technology innovation companies is how to jump from a small group of enthusiasts and achieve mass sales. For this, many theories are extended trying to explain the different behavioral profiles. Therefore, the objective of this article is to analyze the studies on consumer behavior of technological innovations, synthesize the main concepts on this theme, and outline an overview of how this field is configured. To this end, a systematic review, first in the research front and then in the intellectual base was performed. The results indicate a dynamic of articles with more than one model or hybrids that seems to be a trend towards complementing the already consolidated factor theoretical models. This fact implies that these theories are failing to accurately explain the factors that influence a technology to push visionary customers to mass demand.